Power System Planning and Analysis Data Model Research - Zhanfeng Cao; Jian Zhang; He Hao; Xinghua Zhou (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
Power system planning is according to the demand of the social and economic development, energy resources and load distribution, determine the reasonable power structure and strategy. Power grid voltage grade, transmission mode and reasonable space truss structure, etc. Although a large number of literature have studied various aspects of the power planning, but there are few literatures on power system planning comprehensive study, and just theoretical analysis, useless for practical application. This paper analyzes the load forecasting of power system planning, evaluation of power grid and economic evaluation, gives the basic data needed for the analysis and calculation,and provides theoretical guidance for the actual planning work. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.5112